Multibeam bathymetry processed data (Kongsberg EM 2040 working area dataset) of RV ALKOR during cruise AL628, southwest of Bornholm, Baltic Sea - Gazis, Iason-Zois; von See, Tim Benedikt; Greinert, Jens (PANGAEA, 2025)
Multibeam bathymetry processed data (EM 2040 multibeam echosounder) of RV ALKOR during cruise AL628 in the Baltic Sea. The raw data (.kmall) were processed using QPS Qimera software (v 2.6), based on the following workflow: 0.Raw data > 1.Apply correct Sound Velocity Profiles -> 2.Create dynamic surface (shallow Mode) -> 3.Apply Spline Filter (Medium/Strong) > 4. Finalize with manual 2D and 3D editing, -> 5.Export in GeoTIFF format and projected in the UTM33N coordinate system (EPSG:32633). The produced rasters are named AL628_EM2040_'working area'_'resolution in cm'. The bathymetry dataset here is gridded at 0.50 m and 0.75 m resolution. The data products were created in the context of the DAM (German Marine Research Alliance), CONMAR research project.
Keywords: AL628; ALKOR; Baltic Sea; Bathymetry; Bornholm; CONMAR; MBES; MMinE-SwEEPER; Multibeam Echosounder